Composition of Oil from the Seeds of Cassia Sophera Linn. - Mostafa, M; Ahmed, Momtaz; Jahan, Ismet Ara; Choudhury, Jasim Uddin (Bangladesh Journal of Scientific and Industrial Research, 2007)
The oil obtained from the seeds of Cassia sophera Linn was analyzed by GC-MS and a total of 42 compounds have been identified. The major constituents are palmitic acid (22.82 %), linoleic acid (8.32 %), elaidic acid (19.16 %), stearic acid (9.86 %), 5-isopropyl -6-methyl-3-heptyne-2,5-diol (6.44 %), undecyl lauric acid (6.61 %), oleic acid (2.1 %), arachidic acid (3.57 %) and 3α, 7β-dihyodxy -5β, 6β-epoxycholestane (5.9 %). Bangladesh J. Sci. Ind. Res. 42(1), 75-78, 2007